DEVELOPING UNDERSTANDING OF MEDICAL ILLNESS IMPACT ON GRIEF USING THE NOMINAL GROUP TECHNIQUE APPROACH - Siti Nordarma Ab Rahman; Nor Shafrin Ahmad (Journal of Islamic, Social, Economics and Development, 2024)
This study comprehensively analyzes the impact of medical illness on emotional, physical, cognitive, and social well-being over the past two decades, aiming to develop effective support systems. Utilizing a mixed-methods approach, quantitative surveys and qualitative interviews were conducted with individuals experiencing various medical conditions. Findings reveal significant emotional distress, with 83.3% reporting pervasive sadness and frequent crying and substantial physical impacts, such as fatigue and disrupted sleep, affecting 90.0% of participants. Cognitive impairments, including difficulties in concentration and memory, were significant for 85.0%, while social challenges, like isolation and strained relationships, impacted 76.7%. Coping strategies varied, with notable reliance on religious beliefs and mindfulness techniques. The discussion emphasizes the urgent need for robust support systems addressing emotional, physical, cognitive, and social needs, given the high prevalence of these impacts. Despite diverse coping mechanisms, improvements in support from friends and workplaces are critical. The study advocates for comprehensive, multi-dimensional support systems to ensure holistic care for individuals dealing with medical illness, ultimately enhancing their quality of life. This research lays the groundwork for future studies and the development of tailored support strategies.